Dissimilar metal joining and structural repair of ZE41A-T5 cast magnesium by the cold spray (CS) process. Issue 2 (25th January 2018) - Champagne, Victor; Kaplowitz, Dan; Champagne, Victor Kenneth; Howe, Chris; West, Michael K.; McNally, Baillie; Rokni, Michael
ABSTRACT: The ability to join aluminum to magnesium is important for many industries but is a challenge due to the formation of brittle intermetallic compounds (IMCs). This article presents a practical method to join and provide structural repair of cast ZE41A-T5 cast magnesium (Mg) by the cold spray (CS) process using 6061 Aluminum (Al). In this study, the CS process was used to deposit 6061 Al onto ZE41A-T5 Mg substrates, which were subjected to materials testing and characterization. Shear, hardness, and tensile testing were conducted to determine bond integrity at the dissimilar metal joint. Electron and optical microscopy were performed to analyze the interface and microstructure. A review of dissimilar metal joining techniques is provided for comparative purposes, and the unique bonding mechanisms of cold spray are discussed because of its relevance to the results obtained. Results showed that the cold spray process limited the formation of Mg2 Al3 and Mg17 Al12 intermetallic compounds and the bond strength of the dissimilar metal joints created by the cold spray process, had an ultimate tensile strength, hardness, and shear strength comparable to the weakest material being joined (Mg). This study serves to demonstrate the potential of the cold spray process to create high strength dissimilar joints and provide structural repair between Mg and Al.